Problematika Pengelolaan Masjid di Kecamatan Kisaran Barat Kabupaten Asahan - Aidil Zihad; Hasnun Jauhari Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mosques are places of worship for Muslims, so things that facilitate the implementation of worship and the character of the mosque must also be considered, so management is needed. The aim of the research is how to manage a mosque properly and in an orderly manner according to conditions, as well as the role of administrators in making the mosque prosperous. This research is a type of field research, the research approach used in this research is a qualitative approach or descriptive approach. The informants for this research consisted of heads of the Idarah, Imarah and Riayah fields. The research results show that mosque management does not really understand how mosques are managed, so that to optimize the role and function of mosques today, an organizational structure is needed to know how mosques actually function based on Islamic civilization, mosques are not just places for religious and cultural activities, but is an institution that is a place for developing Muslim communities and families, so that optimal training is needed for all members of the mosque organization in interpreting the true function and role of the mosque so that it can reduce problems in managing the mosque properly. The solution to the problem of mosque management is that it is hoped that the mosque management will know the duties and functions of each administrator, and that the management and the community will discuss every decision taken for the progress of the mosques in West Kisaran District, Asahan Regency